Kinematics and kinetics throughout the entire acceleration phase of 60-m sprints in different footwear conditions - Hsiao, H.-W.; Nagahara, R.; Fuchs, P. X. (Journal of Sports Sciences, 2025)
Footwear influences force production, impact absorption, and sprint performance. While research has examined footwear effects on sprint times and kinematics, effects on ground reaction forces during acceleration remains unclear. This study investigated how barefoot, running shoes, and spiked shoes affect sprint biomechanics throughout acceleration. Seventeen male sprinters performed 60-meter sprints in barefoot, shod, and spiked conditions. Fifty force plates recorded ground reaction forces and spatiotemporal variables over the first 50 meters. Repeated-measures ANOVA tested differences between conditions, while statistical parametric mapping (SPM) identified when discrepancies occurred. Maximum speed (p < .001, np2 = .500) and 60-m time (p < .001, np2 = .632) were the best in spiked, with comparable performance between barefoot and shod. Barefoot sprinting demonstrated higher step frequency (p < .001, np2 = .592) and shorter contact time (p < .001, np2 = .542) compared to shod and spiked. Spiked sprinting generated the largest braking and propulsion forces and impulses (p < .001, np2 = .505-.590). Shod generated larger vertical impulse (p < .001, np2 = .659) than barefoot and spiked. SPM results underscored the need to investigate sprint kinetics across acceleration stages and suggested the potential for optimising footwear based on sport-specific sprint distances. The study provided insights in short-distance sprints and highlighted footwear effects on sprint performance and mechanics contributing to overload management considerations.